CALCULATION OF COSTS PROCESSING THE MATERIALS OF ALL-RUSSIA AGRICULTURAL CENSUS - Vladimir P. Bozhko; Vyacheslav V. Shmelev (Статистика и экономика, 2016)
Procedures of costs optimization in the State statistical authorities for processing of materials of All-Russia agricultural census in 2014 are developed. The authors worked out the model which allows accounting the payments of labour of specialists involved with primary processing of the materials.